文章目录
1. What’s Contrapositive?
The contrapositive of a conditional statement is a logically equivalent statement that is formed by negating both the hypothesis (the “if” part) and the conclusion (the “then” part) of the original statement and then reversing their order.
For a given conditional statement in the form of “If P, then Q” (symbolically represented as P → Q), the contrapositive is “If not Q, then not P” (symbolically represented as ¬Q → ¬P).
2. Why Is Contrapositive Important?
-
Logical Equivalence: The contrapositive of a statement is always logically equivalent to the original statement. This means that if the original statement is true, the contrapositive is also true, and vice versa.
-
Proof Method: In mathematics and logic, proving the contrapositive can be a useful technique. If it’s easier to prove the contrapositive of a statement, you can do so and know that the original statement is also proven.
-
Clarity: Sometimes, the contrapositive of a statement is more intuitive or easier to understand than the original statement.
-
Negation: The process of forming the contrapositive involves negating both parts of the conditional. This is different from the inverse (which only negates the hypothesis) and the converse (which only negates the conclusion and switches them).
3. An Example of Contrapositive
For example, consider the statement “If it is raining, then the ground is wet.” The contrapositive of this statement would be “If the ground is not wet, then it is not raining.” If you can prove the contrapositive to be true, you have also proven the original statement to be true.
4. Proof by Contrapositive
Let’s try to prove the following statement: For any two numbers x x x and y y y, x = y x = y x=y if and only if ∀ ϵ \epsilon ϵ> 0, ∣ x − y ∣ |x − y| ∣x−y∣ < ϵ \epsilon ϵ. This asserts that two numbers are equal if they are arbitrarily close (meaning we can choose an arbitrary distance ϵ \epsilon ϵ, and they will be closer to each other than that distance). Since the statement has iff, the implication is bidirectional, and we must prove both directions.
-
x = y ⟹ ∀ ϵ > 0 , ∣ x − y ∣ < ϵ x = y \Longrightarrow \forall\epsilon > 0, |x − y| < \epsilon x=y⟹∀ϵ>0,∣x−y∣<ϵ
Proving this direction is simple. Assume x = y x = y x=y. Then x − y = 0 x − y = 0 x−y=0, so ∣ x − y ∣ = 0 |x − y| = 0 ∣x−y∣=0. Since any ϵ \epsilon ϵ we choose must be greater than 0 0 0, we have ∣ x − y ∣ = 0 < ϵ |x − y| = 0 < \epsilon ∣x−y∣=0<ϵ. Thus ∀ ϵ > 0 , ∣ x − y ∣ < ϵ \forall\epsilon > 0, |x − y| < \epsilon ∀ϵ>0,∣x−y∣<ϵ. -
∀ ϵ > 0 , ∣ x − y ∣ < ϵ ⟹ x = y \forall\epsilon > 0, |x − y| < \epsilon \Longrightarrow x = y ∀ϵ>0,∣x−y∣<ϵ⟹x=y
This statement should make intuitive sense. It’s saying that if the distance between x x x and y y y is less than every positive number, the distance between them must equal 0 0 0. To prove this direction, we’ll use the contrapositive. In this case, the statement ¬ B ⟹ ¬ A \neg B\Longrightarrow \neg A ¬B⟹¬A is x ≠ y ⟹ ¬ ( ∀ ϵ > 0 , ∣ x − y ∣ < ϵ ) . x \neq y \Longrightarrow \neg(\forall\epsilon > 0, |x − y| < \epsilon). x=y⟹¬(∀ϵ>0,∣x−y∣<ϵ)..
Remember from our discussion of logic that we can simplify the right-hand side to x ¬ y ⟹ ∃ ϵ > 0 such that ¬ ( ∣ x − y ∣ < ϵ ) . x \neg y \Longrightarrow \exists \epsilon > 0\ \text{such that}\ \neg(|x − y| < \epsilon). x¬y⟹∃ϵ>0 such that ¬(∣x−y∣<ϵ).
Well, if x ≠ y x \neq y x=y, then x x x must equal y y y plus some number z z z, where z ≠ 0 z \neq 0 z=0. So ∣ x − y ∣ = ∣ z ∣ |x − y| = |z| ∣x−y∣=∣z∣. The absolute value of any non-zero number is always positive, so if we let ϵ = ∣ z ∣ \epsilon = |z| ϵ=∣z∣, then ϵ > 0 \epsilon> 0 ϵ>0 and ∣ x − y ∣ = ϵ |x − y| = \epsilon ∣x−y∣=ϵ. We have shown that ∃ ϵ > 0 \exists \epsilon > 0 ∃ϵ>0 such that ¬ ( ∣ x − y ∣ < ϵ ) \neg(|x − y| < \epsilon) ¬(∣x−y∣<ϵ), so we’re done!
1. 什么是逆否命题?
逆否命题是条件语句的逻辑等价陈述,它通过否定原始语句的前提(“如果”部分)和结论(“那么”部分),然后颠倒它们的顺序来形成。
对于形式为“如果P,则Q”(符号表示为P → Q)的条件语句,其逆否命题是“如果非Q,则非P”(符号表示为¬Q → ¬P)。
2. 为什么逆否命题重要?
-
逻辑等价性:一个陈述的逆否命题总是与原始陈述逻辑等价。这意味着如果原始陈述是真的,那么逆否命题也是真的,反之亦然。
-
证明方法:在数学和逻辑中,证明逆否命题可以是一种有用的技术。如果证明一个陈述的逆否命题更容易,你可以这样做,并知道原始陈述也被证明了。
-
清晰性:有时,一个陈述的逆否命题比原始陈述更直观或更容易理解。
-
否定:形成逆否命题的过程涉及否定条件语句的两部分。这与逆命题(只否定前提)和否命题(只否定结论并交换它们)不同。
3. 逆否命题的例子
例如,考虑陈述“如果下雨,那么地面是湿的。”这个陈述的逆否命题将是“如果地面不湿,那么没有下雨。”如果你能证明逆否命题是真的,你也证明了原始陈述是真的。
4. 通过逆否命题证明
让我们尝试证明以下陈述:对于任意两个数 x x x和 y y y, x = y x = y x=y当且仅当对于所有 ϵ > 0 \epsilon > 0 ϵ>0, ∣ x − y ∣ < ϵ |x - y| < \epsilon ∣x−y∣<ϵ。这断言如果两个数可以任意接近(意味着我们可以选择任意距离 ϵ \epsilon ϵ,它们将比那个距离更接近),那么这两个数就是相等的。由于陈述中有“当且仅当”(iff),含义是双向的,我们必须证明两个方向。
-
x = y ⟹ ∀ ϵ > 0 , ∣ x − y ∣ < ϵ x = y \Longrightarrow \forall\epsilon > 0, |x - y| < \epsilon x=y⟹∀ϵ>0,∣x−y∣<ϵ
证明这个方向很简单。假设 x = y x = y x=y。那么 x − y = 0 x - y = 0 x−y=0,所以 ∣ x − y ∣ = 0 |x - y| = 0 ∣x−y∣=0。由于我们选择的任何 ϵ \epsilon ϵ必须大于 0 0 0,我们有 ∣ x − y ∣ = 0 < ϵ |x - y| = 0 < \epsilon ∣x−y∣=0<ϵ。因此 ∀ ϵ > 0 , ∣ x − y ∣ < ϵ \forall\epsilon > 0, |x - y| < \epsilon ∀ϵ>0,∣x−y∣<ϵ。 -
∀ ϵ > 0 , ∣ x − y ∣ < ϵ ⟹ x = y \forall\epsilon > 0, |x - y| < \epsilon \Longrightarrow x = y ∀ϵ>0,∣x−y∣<ϵ⟹x=y
这个陈述应该直观上是有道理的。它在说,如果 x x x和 y y y之间的距离小于每一个正数,那么它们之间的距离必须等于 0 0 0。为了证明这个方向,我们将使用逆否命题。在这种情况下,陈述 ¬ B ⟹ ¬ A \neg B \Longrightarrow \neg A ¬B⟹¬A是 x ≠ y ⟹ ¬ ( ∀ ϵ > 0 , ∣ x − y ∣ < ϵ ) x \neq y \Longrightarrow \neg(\forall\epsilon > 0, |x - y| < \epsilon) x=y⟹¬(∀ϵ>0,∣x−y∣<ϵ)。
记住我们之前关于逻辑的讨论,我们可以将右侧简化为 x ≠ y ⟹ ∃ ϵ > 0 x \neq y \Longrightarrow \exists \epsilon > 0 x=y⟹∃ϵ>0使得 ¬ ( ∣ x − y ∣ < ϵ ) \neg(|x - y| < \epsilon) ¬(∣x−y∣<ϵ)。
如果 x ≠ y x \neq y x=y,那么 x x x必须等于 y y y加上某个数 z z z,其中 z ≠ 0 z \neq 0 z=0。所以 ∣ x − y ∣ = ∣ z ∣ |x - y| = |z| ∣x−y∣=∣z∣。任何非零数的绝对值总是正的,所以如果我们让 ϵ = ∣ z ∣ \epsilon = |z| ϵ=∣z∣,那么 ϵ > 0 \epsilon > 0 ϵ>0且 ∣ x − y ∣ = ϵ |x - y| = \epsilon ∣x−y∣=ϵ。我们已经证明了 ∃ ϵ > 0 \exists \epsilon > 0 ∃ϵ>0使得 ¬ ( ∣ x − y ∣ < ϵ ) \neg(|x - y| < \epsilon) ¬(∣x−y∣<ϵ),所以我们完成了证明!